Hydride-encapsulated bimetallic clusters supported by 1, 1-dithiolates. Issue 65 (15th July 2020) - Zhong, Yu-Jie; Liao, Jian-Hong; Chiu, Tzu-Hao; Wu, Ying-Yann; Kahlal, Samia; Saillard, Jean-Yves; Liu, C. W.
Abstract : A four-coordinated hydride lying at the center of heptanuclear bimetallic clusters was anisotropically refined to convergence by X-ray crystallography. Abstract : Two mixed-metal hydride clusters, corresponding to x = 3 and 4, were structurally characterized from a set of atomically precise heptanuclear clusters, Cu x Ag7− x (H)S2 P(O i Pr)2 6 ( x = 1–6). An interstitial hydride lying at the center of a tricapped tetrahedral cage was located and refined anisotropically by using X-ray data, and its presence acertained by multinuclear NMR spectroscopy and DFT calculations.